Secrets of next-level entrepreneurs : 11 powerful lessons to thrive in business and lead a balanced life - Brueckmann, Alex (Ascent Audio, 2023)
In Secrets of Next Level Entrepreneurs: 11 Powerful Lessons to Thrive in Business and Lead a Balanced Life, business strategist Alex Brueckmann presents a collection of practical and insightful resources that walk you through how to grow a profitable business while maintaining a healthy and fulfilling life. You'll learn to run your company while, at the same time, contributing to and improving a community and world we all want to live in. In the book, industry leaders offer hyper-specific and actionable advice about issues that dominate the thoughts of every business leader and owner at one point or another, from how to implement environmentally and socially sustainable practices to building high-performance workplace cultures and setting optimal pricing strategies in environments of high inflation. You'll also find: frequently overlooked perspectives and unfamiliar topics that hold huge value for courageous listeners with open minds; strategies for prioritizing self-care while running your business, ensuring you don't neglect yourself while you're taking care of everyone else; and a philosophy that emphasizes the creation of sustainable, profitable businesses that contribute to the health of their founders, employees, stakeholders, and communities.